Structure and Mechanism of the Sodium Polyisoprene Battery - Borowski, Tomasz (Asian Journal of Chemistry, 2010)
The conductive properties of polyisoprene with sodium chlorate can be used at industrial scale as miniature battery. Polymer material modified with sodium chlorate was used to produce sodium polyisoprene battery. The conduc-tivity of such polymer composites for temperatures ranging 273 to 313 K is at a similar level and amounts to 10-4 S cm-1 for polyisoprene at 50 kHz. The conductive battery made of butadiene polymer shows an open circuit voltage of 1.2 V with a short circuit current of 43 mA. The lightness, commonly found material (sodium) and environment-friendly energy are main advantages of sodium polyisoprene battery.